Quantitative comparison of the electromyogram of the swimmer - Lewillie, L. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
The importance of an exact knowledge of the modalities of adaptation of the muscular activity is more important in swimming than in any other physical activity. The problems posed by the water element, the poor efficiency of man who does not obtain 10% of his performance on the dry {1), made that all proposed modifications have to be based more than ever on measurable values.